An ultrastructural study on the ligamentum flavum of the cervical spine in patients with ossification of the posterior longitudinal ligament - Nakama, Sueo; Ihara, Tomomi; Sugamata, Masao; Endo, Teruaki; Ooyama, Motohiko; Hoshino, Yuichi (Medical molecular morphology, 2006)
Some histological analyses of the ossification of the posterior longitudinal ligament (OPLL) have been reported, but no ultrastructural studies of the ligamentum flavum (LF) in patients with OPLL have been published to date. To understand the pathology of the ossification of the spinal ligament, we examined, by electron microscopy, ultrastructural changes in the LF in cases of OPLL and made a comparison with the LF in cervical spondylotic myelopathy (CSM). Subjects were three men and two women with cervical OPLL who underwent longitudinal spinous process-splitting laminoplasty. During surgery, a small piece of the LF was collected from C2-C3 to C7-T1 and was then analyzed by light and electron microscopy. We observed atrophic elastic bundles with a two-layer structure and disarrangement, a partially torn area, the disappearance of microfibrils, and an enlarged interstitium with an irregular alignment of collagen fibrils. We observed some properties of a cell preceding its death: the initial phase may be the disappearance of the plasma-membrane, followed by the scattering of many organellae around its degenerated nucleus. Finally, many extracellular plasma membrane-invested particles that resemble matrix vesicles remain there without phagocytosis. These results suggest that ultrastructural abnormalities exist in the spinal ligament in cases of ossification of the spinal ligament.